Kidney Cancer Principles and Practice - Lara, Primo N.; Jonasch, Eric.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Kidney Cancer: Principles and Practice is a comprehensive and interdisciplinary textbook that encompasses all clinically relevant aspects of the disease. This new edition has been extensively updated and includes brand new material covering the most recent developments in kidney cancer diagnosis and therapy. The user-friendly and clinically oriented content of the book guarantees that it will be of great interest to a wide range of medical professionals, and every effort has been made to ensure that contributions are both easy to understand and directly related to patient care. Content presentation departs from the usual dense chapter format featuring a lengthy series of paragraphs. Instead, each chapter contains several boxed sections, including one that summarizes essential "take home points" for the busy clinician and another that presents a patient-oriented case highlighting the clinical application of elements discussed in that chapter. In addition, accessible original images, illustrations, and diagrams (some in full color) are used to simplify particularly complex material. This book will be of value for clinicians, researchers, residents, fellows, students, and knowledgeable lay people. The contributors comprise an international group of authors with expertise in kidney cancer epidemiology, molecular biology, pathology, diagnosis, clinical features, staging, prognostic and predictive factors, surgery, systemic therapy, and emerging investigational approaches, among others.  .
Part 1: Epidemiology and Biology Epidemiology of Kidney Cancer -- Pathological Classification -- Molecular Biology of Kidney Cancer --  Biomarkers for Kidney Cancer -- Genetic Heterogeneity of Kidney Cancer -- Metabolic Basis of Kidney Cancer. Part 2: Clinical Considerations Clinical Presentation and Staging.-  Hereditary Kidney Cancer.  Part 3: Surgical and Local Control Modalities Surgical Approaches to Early Stage Kidney Cancer -- Cytoreductive Nephrectomy -- Metastasectomy -- Energy Ablative Techniques in Kidney Cancer -- The Role of Radiation Therapy in Kidney Cancer. Part 4: Systemic Therapy Considerations Adjuvant Systemic Therapy -- Cytokines and Vaccine Therapy -- PD1 and PDL1 Targeted Therapy -- Angiogenesis Inhibitor Therapy -- The Role of mTOR inhibitors and PI3K Pathway Blockade -- Sequential versus Combination Strategies -- Presurgical Therapy in Kidney Cancer -- Toxicity Management for Patients on Targeted Therapies -- Emerging Agents in Kidney Cancer.
Keywords: Oncology .; Surgery; Cancer research; Internal medicine; Pathology; Oncology; Surgery; Cancer Research; Internal Medicine; Pathology